Comparison of intraocular pressure and pupil diameter after sedation with either acepromazine or dexmedetomidine in healthy dogs. (September 2018) - Micieli, Fabiana; Chiavaccini, Ludovica; Lamagna, Barbara; Vesce, Giancarlo; Santangelo, Bruna
Abstract: Objective: To compare intraocular pressure (IOP) and pupillary diameter (PD) following intravenous (IV) administration of dexmedetomidine and acepromazine in dogs. Study design: Prospective, randomized experimental trial. Animals: A group of 16 healthy adult dogs aged (mean ± standard deviation) 4.9 ± 3.3 years and weighing 15.7 ± 9.6 kg, without pre-existing ophthalmic disease. Methods: IV dexmedetomidine hydrochloride (0.002 mg kg –1 ; DEX) or acepromazine maleate (0.015 mg kg –1 ; ACE) was administered randomly to 16 dogs (eight per group). The IOP and PD, measured using applanation tonometry and Schirmer's strips mm scale, respectively, and the heart rate (HR), systolic (SAP), mean (MAP) and diastolic (DAP) arterial pressures and respiratory rate ( f R ) were recorded at baseline, at time of injection, and then 5, 10, 15, 20 and 25 minutes after injection. A single ophthalmologist, unaware of treatment, performed all measurements under consistent light conditions. Values were compared with baseline and among treatments using a multivariate mixed-effects model ( p ≤ 0.05). Results: The IOP was significantly lower in the DEX group compared with the ACE group at 10 ( p < 0.01) and 15 minutes ( p < 0.01) after drug injection. PD was significantly smaller compared to baseline for the entire duration of the study ( p < 0.01) in both groups. Dogs in the DEX group had significant lower HR ( p < 0.01) and f R ( p < 0.01), higher SAP ( p < 0.01) and DAP ( p < 0.01) at all time points, and higher MAP ( p < 0.01) during the first 15 minutes following drug injection in comparison with the ACE group. Conclusions and clinical relevance: Our results suggest that premedication with IV dexmedetomidine temporarily decreases IOP when compared with IV acepromazine. Both drugs cause miosis.